Elevated temperature and water stress accelerate mesocarp cell death and shrivelling, and decouple sensory traits in Shiraz berries - Bonada, Marcos; Sadras, Victor Oscar; Moran, Martin; Fuentes, Sigfredo (2018)
Both water deficit and elevated temperature are likely to accelerate shrivelling in Shiraz berries with consequences for fruit yield and quality. The process of shrivelling is partially related to mesocarp cell death and it has been proposed that enhancement of berry flavour and aroma also correlates with mesocarp cell death. However, the combined effects of water deficit and elevated temperature on berry shrivelling, mesocarp cell death and berry sensory traits are unknown. We tested the hypotheses that (1) the effects of water deficit and elevated temperature on the dynamics of mesocarp cell death and shrivelling are additive, and that (2) faster cell death, as driven by warming and water deficit, negatively contributes to grape sensory balance. Using open-top chambers to elevate day and night temperature, we compared heated vines against controls at ambient temperature. Thermal regimes were factorially combined with two irrigation regimes, fully irrigated and water deficit, during berry ripening. The dynamic of cell death was characterised by a bilinear model with three parameters: the onset of rapid cell death and the rate of cell death before and after the onset of rapid cell death. Statistical comparison of these three parameters indicated that there was not interaction between water and temperature on the dynamics of berry mesocarp cell death. Warming advanced the onset of cell death by ~9 days (P = 0.0002) and water stress increased the rate of cell death in the period post onset (P = 0.0007). Both water stress and elevated temperature increased the proportion of cell death and shrivelling at harvest. An interaction between water deficit and elevated temperature was found whereby the onset of berry net water loss was advanced by elevated temperature under water deficit but not in the fully irrigated treatment. Sensory traits typical of ripened berries were associated with higher cell death; however, warming and water deficit hastened ripening and altered the balance of berry sensory traits.